2022
DOI: 10.3389/fphar.2022.901234
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin Attenuates Renal Tubular Injury and Mitochondrial Damage in Diabetic Nephropathy Partly via Regulating Sirt1/PGC-1α Pathway

Abstract: Mitochondrial abnormality is one of the main factors of tubular injury in diabetic nephropathy (DN). Formononetin (FMN), a novel isoflavonoid isolated from Astragalus membranaceus, has diverse pharmacological activities. However, the beneficial effects of FMN on renal tubular impairment and mitochondrial dysfunction in DN have yet to be studied. In this study, we performed in vivo tests in Streptozotocin (STZ) -induced diabetic rats to explore the therapeutic effects of FMN on DN. We demonstrated that FMN coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…[ 30 ] Formononetin further develops albuminuria and renal histopathology and weakens renal cylindrical injury and mitochondrial harm in DN by regulating the Sirt1/PGC-1α pathway. [ 31 ] Quercetin, with anti-inflammatory and antioxidant effects, can be metabolized into glucuronides, sulfates, and methyl conjugates. [ 32 ] Isorhamnetin is not only used to prevent cardiovascular diseases but also has good pharmacological effects on anti-tumor, anti-bacterial, and anti-proliferative aspects.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…[ 30 ] Formononetin further develops albuminuria and renal histopathology and weakens renal cylindrical injury and mitochondrial harm in DN by regulating the Sirt1/PGC-1α pathway. [ 31 ] Quercetin, with anti-inflammatory and antioxidant effects, can be metabolized into glucuronides, sulfates, and methyl conjugates. [ 32 ] Isorhamnetin is not only used to prevent cardiovascular diseases but also has good pharmacological effects on anti-tumor, anti-bacterial, and anti-proliferative aspects.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Formononetin can alleviate nephrotoxicity in methotrexate-, cisplatin-and gentamicin-induced kidney injury and DKD (Aladaileh et al, 2019;Oza and Kulkarni, 2019;Hao et al, 2021;Althunibat et al, 2022). Formononetin promotes mitochondrial biogenesis via Sirtuin-1-PGC-1α pathway, which plays an important role in kidney protection (Rasbach and Schnellmann, 2008;Huang et al, 2022e). Formononetin treatment could attenuate tubular cell apoptosis and podocyte injury, then further to decrease Frontiers in Pharmacology frontiersin.org urinary albumin excretion and ameliorate the progression of DKD (Huang et al, 2022e).…”
Section: Formononetinmentioning
confidence: 99%
“…Formononetin promotes mitochondrial biogenesis via Sirtuin-1-PGC-1α pathway, which plays an important role in kidney protection (Rasbach and Schnellmann, 2008;Huang et al, 2022e). Formononetin treatment could attenuate tubular cell apoptosis and podocyte injury, then further to decrease Frontiers in Pharmacology frontiersin.org urinary albumin excretion and ameliorate the progression of DKD (Huang et al, 2022e).…”
Section: Formononetinmentioning
confidence: 99%
“…Mitochondrial fragmentation is an important pathogenic feature of renal tubular cell injury, and FIS1 and DRP1 play an important role in mitochondrial fission. In renal tubular cells with DKD, mitochondria are fragmented and FIS1 is increasing, while downregulation of FIS1 can improve mitochondrial morphology and reduce apoptosis of renal cells [ 149 , 150 ]. It has been shown that pharmacological inhibition of DRP1 expression and protection of mitochondria from excessive division can effectively stop progression of DKD [ 99 ].…”
Section: Fis1- and Drp1-dependent Mitochondrial Dynamics In Kidney Di...mentioning
confidence: 99%
“…Polydatin (PD) is a resveratrol glycoside that protects kidney function in patients with diabetic nephropathy, and PD is able to inhibit podocyte injury by suppressing DRP1 expression and mitochondrial fragmentation [ 159 ]. Formononetin (FMN) is a novel isoflavonoid constituent isolated from Astragalus membranaceus; it can reduce mitochondrial fission protein, increase mitochondrial fusion protein, and improve mitochondrial damage in diabetic nephropathy [ 150 ]. P110 is an inhibitor of DRP1 and FIS1 interaction and can improve mitochondrial damage by blocking the interaction between the two fissions [ 160 ].…”
Section: Drugs Targeting Fis1 and Drp1 And Their Role In Kidney Diseasementioning
confidence: 99%